Small scale industry in the production of tea tree and citronella essential oil/ Abdul Samat Gany … [et.al.] - Gany, Abdul Samat; Sapiie, Affendi; Chabu, James; Ibrahim, Khalik (2002)
Malaysia, a country blessed with a diverse range of flora and fauna and a potpourri of cultures, augers well for the development of herbal industry. In fact, study has shown that Malaysia is one of the only 12 countries in the world with a tremendous potential to be a global player in this industry. It is against this background that the Group has decided to choose this particular industry as its Applied Business Project. Herbal industry involves a wide range of products. However, this project is confined only to the viability of producing and marketing of essential oils, specifically Citronella and Tea Tree oils, as a business venture. The project encompasses the planting, harvesting, extracting and the marketing of these oils.